Could arid and semi-arid abandoned lands prove ecologically or economically valuable if they afford greater soil organic carbon storage than afforested lands in China's Loess Plateau?. (December 2020) - Cao, Jianjun; Wei, Chen; Adamowski, Jan F.; Zhou, Junju; Liu, Chunfang; Zhu, Guofeng; Dong, Xiaogang; Zhang, Xiaofang; Zhao, Huijun; Feng, Qi
Highlights: Soil carbon storage in afforested lands and in abandoned lands was compared in arid and semi-arid area, China Carbon storage to a 1.0 m soil depth under the abandoned lands (80.58 Mg ha -1 ) was significantly higher than under the afforested stands (71.82 Mg ha -1 ) As the loss of arable lands to urbanization worsening food security, focus should be placed on the economic use of abandoned lands through consolidation Abstract: As in the rest of the world, China assumed afforestation was an effective means of helping to mitigate the negative impacts of global warming, soil erosion and soil degradation, and returned large areas of farmland to woodland. At the same time, due to industrialization and urbanization, large tracts of arable land were abandoned, especially on the Loess Plateau. To explore which land use type has greater potential to absorb carbon dioxide from the atmosphere and thus provide suggestions for land use policy in this region, a comparison of soil organic carbon storage under abandoned and afforested lands was undertaken in the northwest part of the Loess Plateau (Huining County, Gansu province, China). The soil water content, pH, soil bulk density, soil organic carbon content and overall organic carbon storage of soils (0-1.0 m depth) were measured in each of 21 plots (10 m × 10 m) on the abandoned (apricot trees) lands, and 21 similar plots on the afforested lands. Soils under the two land use types showed no significant differences in gravimetric water content or pH up to 1.0 m in depth. The soil bulk density, organic carbon content and organic carbon storage under the abandoned lands (1.18 Mg m -3, 7.07 g kg -1, and 80.58 Mg ha -1, respectively) were all significantly higher than under the afforested lands (1.13 Mg m -3, 6.62 g kg -1, and 71.8 Mg ha -1, respectively). Although benefits such as strong soil carbon fixation and lower water consumption were greater in the abandoned lands, this does not imply that afforested lands should be converted into abandoned lands, as they can provide wind barriers, reduce soil erosion, and maintain high biodiversity. However, given the integration of urban and rural development policies, as well as worsening food security issues attributable to the loss of arable lands to urbanization, some focus should be placed on the use of abandoned lands through consolidation.